Dietary fibre prevalence and its role in human nutrition - Csatári, Gábor; Kovács, Szilvia (Acta Agraria Debreceniensis, 2022)
The role of dietary fibre and its impact on health is increasing. It is worth noting that their beneficial effects on the body are becoming more widely known, but their consumption is still below the recommended daily intake from food. Dietary fibre, as a class of compounds, includes a mixture of plant carbohydrate polymers, both oligosaccharides and polysaccharides. Dietary fibre has been linked to a number of diseases, as its consumption can reduce the risk of cardiovascular disease and type 2 diabetes. They influence the composition of the bacteria present in the human gut. Consuming the right quantity and quality of dietary fibre can play a role in the prevention of certain types of cancer. Nowadays, it is common to produce various fibre-enriched foods, called functional foods, because of the beneficial effects they have previously had on the body. In the present work we want to give a general description of dietary fibre and its role in the body.